The role of increased lipoprotein (a) and apolipoprotein B-100 levels, and their link to cholesterol and triglyceride concentration in coronary heart disease patients - G. G. Arabidze; E. O. Skryabina; I. G. Inaneishvili; O. I. Afanasyeva (Кардиоваскулярная терапия и профилактика)
Aim. To investigate lipid profile, lipoprotein (a) [Lp(а)] and apolipoprotein В-100 (apo В-100) levels in coronary heart disease (CHD) patients. To identify significant CHD predictors and their association with cholesterol (CH) and triglyceride (TG) levels. Material and methods. In total, 575 patients (main group), aged 66,56±12,51 years, with verified CHD were included, as well as 86 individuals (control group), aged 55,47±11,47 years, without cardiovascular disease (CVD). Results. Levels of apo B-100 – 128,17 mg/dl (р<0,00001) and Lp(a) – 27,6 mg/dl (р<0,007) were significantly higher in all CHD patients than in control group. Lp(a) level was significantly higher in acute coronary syndrome (ACS) patients, comparing to control group (р<0,02). Increased apo B-100 leve, 130,9±46,5 mg/dl was a significant (р<0,00001) risk factor (RF) for ACS in CHD patients. There was a significant correlation between Lp(a) (р<0,00003) or apo B-100 (р<0,00001) levels and CH or TG concentrations in CHD individuals. Conclusion. Lp(a) and apo B-100 levels were significant RF for CHD (including acute myocardial infarction) development. Maximal concentration of Lp(a) was observed in CHD patients with hypercholesterolemia (HCH); maximal apo B-100 level – in CHD and hypertriglyceridemia participants.